2019
DOI: 10.3389/fphar.2019.00482
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Ventilator-Associated Pneumonia in Critically III Patients

Abstract: Ventilator-associated pneumonia (VAP), a hospital acquired pneumonia that occurs more than 48 h after mechanical ventilation, is a common complication of mechanical ventilation with a high mortality rate. VAP can cause patients to have difficulty weaning off the ventilator and to stay in the hospital longer, which results in a huge financial burden to patients and a huge demand for medical resources. Several strategies, such as drugs including chlorhexidine, β-lactam antibiotics and probiotics, have been used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
120
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(138 citation statements)
references
References 57 publications
9
120
0
9
Order By: Relevance
“…This may indicate that the decision to extubate was more appropriate in the intensivist group. As the rate of early extubation increased and the duration of mechanical ventilation was shortened, we expected the incidence of VAP and delirium to decrease because both are associated with a longer mechanical ventilation time [14,15]. Although the incidence of VAP was lower in the intensivist group, as we expected, this difference did not reach statistical significance.…”
Section: Kjtcvsmentioning
confidence: 85%
“…This may indicate that the decision to extubate was more appropriate in the intensivist group. As the rate of early extubation increased and the duration of mechanical ventilation was shortened, we expected the incidence of VAP and delirium to decrease because both are associated with a longer mechanical ventilation time [14,15]. Although the incidence of VAP was lower in the intensivist group, as we expected, this difference did not reach statistical significance.…”
Section: Kjtcvsmentioning
confidence: 85%
“…Delayed gastric emptying leads to nutritional intolerance and gastric reflux, incr easing the risk of VAP [43,44]; An indwelling gastric tube can impair cardiac sphincter function and increase the chance of gastric fluid reflux, leading to aspiration. Bacteria in the stomach may coloni ze the pharynx through the antiperistaltic action of the stomach and along the gastric tube and ente r the lower respiratory tract, resulting in infection [47]; Interestingly, CVC placement was also found to be a risk factor for VAP in this meta-analysis. A survey of device-associated infection rates inad ult ICUs in Catalonia showed that CVC placement ranged from 18% to 98% (mean 65%) [48].…”
Section: Discussionmentioning
confidence: 70%
“…On the other hand, the analysis also indicated that the development of VAP in a cohort of patients with COPD admitted to the ICU significantly increased mortality, the duration of mechanical ventilation and length of ICU stay as compared with those of patients with COPD but without VAP. According to previous studies, COPD is a commonco-morbidity in patients with VAP (18,19). However, it was demonstrated that the presence of COPD is not associated with a higher incidence of VAP as compared with that of patients without COPD (1,12).…”
Section: Discussionmentioning
confidence: 97%